LEGAL PROTECTION FOR PRISONERS IN ILLNESS WHO REQUIRE HOSPITAL TREATMENT - Riza Wira Pratiwi Lumbantoruan; Henry Aspan; Siti Nurhayati (PT. Radja Intercontinental Publishing, 2024)
Indonesia has ratified the Convention Against torture and other cruel, inhuman or degrading treatment or punishment (adopted and opened for signature and accession by General Assembly Resolution 39/46 of 10 December 1984 into Law Number 5 of 1998 which came into effect on 28 September 1998 . The Convention relates to the promotion and protection of the rights of prisoners which are accommodated in the prohibition of torture and other treatment or punishment that is cruel, inhuman and degrading to human dignity. Suspects who are detained and experiencing health problems, it is in the interests of investigative examinations and for the smooth running of examination of suspects requires treatment. In Indonesia, regulations regarding the rights of prisoners in the health sector are contained in several laws, including based on the decision of the Minister of Justice of the Republic of Indonesia No. 1995 concerning Corrections, Government Regulation Number 32 of 1999 concerning Requirements and Procedures for Implementing the Rights of Inmates. Health services for prisoner patients are carried out in a promotive, preventive, curative and rehabilitative manner, the implementation of which is currently not yet running optimally, this is indicated by the fact that health services for prisoners have not been carried out on a scale, integrated, integrated and sustainable basis. The implementation of care for prisoners in sick conditions who require hospital treatment will run well if in the system of fulfilling the rights of prisoners they are positioned not only as objects of detention, but also as active participants. In this case, prisoners themselves also determine the implementation of their rights.